Urgensi Revisi Undang-undang Anti Monopoli Indonesia Studi Perbandingan Fair Trade Commission Jepang - Muhammad Habib; David Brilian Sunlaydi; Yusa Pridasa; Hanna Oktaviana Sutopo (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The revision of the antitrust law is very much needed to keep business competition in Indonesia running well and smoothly, it is necessary to revise it so that the legal umbrella for these business actors is maintained and its relevance in the current era, there are many benefits that can be obtained from the law. However, this antitrust law cannot be separated from the weaknesses contained in the law, therefore this article discusses the weaknesses of legal subjects, merger notices and procedural law applicable in business competition law in Indonesia. This study uses a normative method that is carried out to find the truth scientifically, and the approach used in this study uses a statutory approach to find out which regulations still have deficiencies in their normalization and a comparative approach can find out the regulations in Japan which have similarities and differences. in the regulation, it can be used as material to carry out reforms to improve the antitrust law in Indonesia. The results of this study are expected to find interests that require immediate revision of the antitrust law in Indonesia in order to create a fair business competition climate and have an impact on legal certainty and maintaining consistency in the harmonization of the applicable laws and regulations..